2021
DOI: 10.3389/fimmu.2021.639221
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PD1+Vδ1+γδ T Cell Predicts Fertility in Endometrial Polyp Patients of Reproductive-Age

Abstract: Clinically, immune cell function is correlated with pathogenesis of endometrial polyp (EP) and infertility of women of reproductive-age. However, the underlying immune cell hallmark in EP patients remains unclear. Here, we focused on analyzing circulating immune cells, and attempted to reveal the correlation between peripheral immune cell functional phenotypes and fertility in EP patients. Through comparison of circulating CD4+/CD8+ T cells, NK cells, and γδ T cells between 64 EP patients and 68 healthy female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…32 There are several studies focusing on the role of peripheral blood γδ T in predicting the failure of pregnancy. [33][34][35] In particular, the mechanisms by which decidual γδ T cells contribute to the pathogenesis of RPL are not well defined. 31 PD-1 regulates the effector function of T cells under normal physiological and pathological conditions, and maintains immune homeostasis by limiting protective immunity, [36][37][38] while PD-L1, the ligand of PD-1, is usually highly expressed on tumor cells and other hematopoietic cells 39,40 protecting target organs against autoimmune attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 There are several studies focusing on the role of peripheral blood γδ T in predicting the failure of pregnancy. [33][34][35] In particular, the mechanisms by which decidual γδ T cells contribute to the pathogenesis of RPL are not well defined. 31 PD-1 regulates the effector function of T cells under normal physiological and pathological conditions, and maintains immune homeostasis by limiting protective immunity, [36][37][38] while PD-L1, the ligand of PD-1, is usually highly expressed on tumor cells and other hematopoietic cells 39,40 protecting target organs against autoimmune attack.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study found that RANKL promoted the polarization of γδT cells on the decidua to Foxp3 + γδΤ cells to maintain pregnancy 32 . There are several studies focusing on the role of peripheral blood γδ T in predicting the failure of pregnancy 33‐35 . In particular, the mechanisms by which decidual γδ T cells contribute to the pathogenesis of RPL are not well defined 31 …”
Section: Discussionmentioning
confidence: 99%
“…A history of infertility has a significantly positive connection with CE in patients with EP 21 . Inflammation‐associated cytokines (including interleukin‐6, interleukin‐17, interleukin‐1β, tumor necrosis factor‐α, and interferon‐γ) are activated by chronic inflammation resulting from CE 20–22 . EP is a lesion of local inflammation, and CE activates the inflammatory cytokines that contribute to the development of EP 20 .…”
Section: Discussionmentioning
confidence: 99%
“…20 The local inflammatory environment of the endometrium has an association with the development of recurrent EP after polypectomy. 22 We defined having at least two polyps as multiple polyps.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation